Czy każde dziecko chore na astmę powinno stosować lek antyleukotrienowy – przegląd badań klinicznych - Majak, Paweł; Stelmach, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
In the treatment of persistent asthma, randomized controlled trials have shown leukotriene inhibitors to be more effective than placebo but less effective than inhaled corticosteroids. The use of leukotriene inhibitors has shown an inhaled-steroid-sparing effect, a reduction in need for systemic steroid treatment, or cost savings. In the light of the results of our study montelukast seems to be the best therapeutic option for exercise-induced asthma. Interestingly, montelukast may have some preventive activity against viral-induced asthma exacerbations. There is strong evidence for clinical effectiveness of montelukast in all asthma phenotypes, which makes this drug the most universal anti-asthma treatment option. As established for all drugs commonly used in the treatment of asthma, there is individual variability also in response to montelukast. Therefore, the therapeutic decision in each case should be associated with calculation of the risk/benefit ratio.